Exchange flow in a highly stratified fjord in drought conditions - Pinilla, Elias; Ross, Lauren; Pérez-Santos, Iván (Frontiers in Marine Science, 2024)
Fjords are known for their biodiversity and abundant aquaculture resources. However, climate and anthropogenic pressures are altering fjord biological, physical, and chemical processes that will undoubtedly change the ecosystem. To investigate the impact of climate change on fjord functioning, this study examines the impacts of drought conditions on the physical dynamics variations in a fjord known for its bolstering aquaculture industry in Northern Chilean Patagonia, the Reloncaví Fjord (41.5° S). Utilizing a high-resolution hydrodynamic model and the Total Exchange Flow (TEF) framework, this study assesses the differential influences of river discharge, tidal forces, and surface wind across diverse hydrological conditions for a dry (2016) and a typical year (2018). The analysis for 2016 shows decreased TEF and a shift in volume transport toward higher salinity classes when compared to 2018. In 2018, river discharge dominated exchange flow dynamics, accounting for 74% of the total TEF variability, while tidal and wind contributions were 17% and 9%, respectively. The summer of 2016 exhibited a notable shift in the influence of tidal and wind forcing on the exchange flow, increasing to 21% and 16%, respectively. This change underscores the importance of tides and wind in shaping exchange flow dynamics under conditions of reduced freshwater input. The enhanced influence of wind in 2016 facilitated destratification events where subsurface waters high in salinity were mixed with the fresh surface layer, which could have implications for ecosystem dynamics. Utilizing logistic regression models, we established a significant relationships between stratification levels and the occurrence of harmful algal blooms (HABs), particularly for Pseudchatonella and Alexandrium catenella. For Pseudchatonella, lower stratification levels were associated with a higher probability of HAB events during summer. Conversely, Alexandrium catenella was more closely associated with higher stratification levels during spring, linked to increased river discharge. This statistical relationship provides valuable insights into how environmental conditions may favor the proliferation of specific HABs species. The results of this study indicate that severe harmful algal bloom events in Northern Patagonia could increase in frequency as climate change progresses, highlighting the importance of considering local environmental dynamics in addition to larger-scale climatic indices when studying HABs.